2011
DOI: 10.1002/adma.201102313
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Nanotheranostics: Improving Imaging and Therapy by Targeted Delivery Across Biological Barriers

Abstract: Cancer nanotheranostics aims to combine imaging and therapy of cancer through use of nanotechnology. The ability to engineer nanomaterials to interact with cancer cells at the molecular level can significantly improve the effectiveness and specificity of therapy to cancers that are currently difficult to treat. In particular, metastatic cancers, drug-resistant cancers, and cancer stem cells impose the greatest therapeutic challenge that requires targeted therapy to treat effectively. Targeted therapy can be ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
334
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 456 publications
(338 citation statements)
references
References 405 publications
(310 reference statements)
1
334
0
3
Order By: Relevance
“…33 It is reported that the NPs with 30−200 nm in hydrodynamic diameter accumulate with high efficiency in many solid tumors by EPR effect. 34 Distinguishingly, the fenestrations in the liver sinusoidal endothelium facilitate the substrate transfer into space of Disse between the liver sinusoid and hepatocytes in normal liver. The diameter of the fenestrations is ~78 ± 12 nm in wild-type mice.…”
Section: Enhanced Permeability and Retention (Epr) Effect In Hccmentioning
confidence: 99%
“…33 It is reported that the NPs with 30−200 nm in hydrodynamic diameter accumulate with high efficiency in many solid tumors by EPR effect. 34 Distinguishingly, the fenestrations in the liver sinusoidal endothelium facilitate the substrate transfer into space of Disse between the liver sinusoid and hepatocytes in normal liver. The diameter of the fenestrations is ~78 ± 12 nm in wild-type mice.…”
Section: Enhanced Permeability and Retention (Epr) Effect In Hccmentioning
confidence: 99%
“…These characters are known as the enhanced permeability and retention (EPR) effects that have been widely used to enhance the tumor selectivity of antitumor nanomedicines [6][7][8]. It was reported that with time the concentration of some intravenously (IV) administered nanosized anticancer drugs at the tumors could become several folds higher than that in normal tissues [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Further, such nanocarriers can overcome chemoresistance by circumventing activation of extruding mechanisms and by protecting the drug from lysosomal degradation. 11,12 Nanoparticles can reach and accumulate within the tumor site passively, exploiting leaky and imperfect tumor neovascularization and defective lymphatic drainage, 13,14 or actively, by functionalizing the surface of the nanoparticles with ligands specifically directed to targets expressed on tumor cells. [15][16][17][18] Before a nanomaterial can be deemed a suitable theranostic tool, it is necessary to assess its ability to enter the cell, to reach the desired intracellular compartment (wherein the drug will be liberated), and to remain in the cell for a time period sufficient to allow adequate diagnostic and therapeutic functions.…”
Section: Introductionmentioning
confidence: 99%